2015
DOI: 10.1016/j.jvs.2015.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of polytetrafluoroethylene-covered stent versus bare-metal stent in the primary treatment of severe iliac artery obstructive lesions

Abstract: Overall, the use of CSs for severe iliac lesions has similar early and midterm outcomes compared with BMS. In a subcategory of TASC II D lesions with long-segment severe stenosis of both the common and external iliac arteries, CS should be considered as the primary line of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 14 publications
1
44
0
Order By: Relevance
“…The COBEST is the only randomised controlled trial comparing the use of CS and BMS for complex lesions classified by the TASC II as class C and D. In this study, there was a significantly better patency in favour of CS both at 1 year 6 and at 5 years. 7 Recently it was reported, 8 in a single centre experience, that the use of a CS rather than a BMS has better early and midterm outcomes in cases of TASC D lesions with long segment severe stenosis involving both the common iliac artery (CIA) and the external iliac artery (EIA). However, no previous studies have focused on the outcomes of CS versus BMS in the primary treatment of IAOs only.…”
Section: Introductionmentioning
confidence: 99%
“…The COBEST is the only randomised controlled trial comparing the use of CS and BMS for complex lesions classified by the TASC II as class C and D. In this study, there was a significantly better patency in favour of CS both at 1 year 6 and at 5 years. 7 Recently it was reported, 8 in a single centre experience, that the use of a CS rather than a BMS has better early and midterm outcomes in cases of TASC D lesions with long segment severe stenosis involving both the common iliac artery (CIA) and the external iliac artery (EIA). However, no previous studies have focused on the outcomes of CS versus BMS in the primary treatment of IAOs only.…”
Section: Introductionmentioning
confidence: 99%
“…major amputation, renal failure and death) and poor long-term durability [5][6][7][8] . There is great interest in developing novel medical therapies for the leg symptoms of PAD.…”
mentioning
confidence: 99%
“…Interestingly, in a study by Humphries et al 7 in 2014 looking strictly at percutaneous iliac artery interventions, the use of covered balloon-expandable stents conferred a reduction in patency rates compared with bare-metal balloon-expandable stents. In two separate series by Piazza et al 8 and Psacharopulo et al, 9 it was demonstrated that covered stents for severe iliac lesions had patency rates similar to those of bare-metal stents. However, when both of these groups of investigators looked specifically at long-segment TASC D lesions, covered stents actually had better patency rates than baremetal stents in this subgroup of patients.…”
Section: Discussionmentioning
confidence: 96%